Civil Society - State Relations: Investigating the Discourse and Practice of Non-Governmental Organizations (NGOs) in Indonesia - Suryadi, Adi; Misran, Misran; Angkananon, Chumphon (Jurnal Studi Pemerintahan, 2025)
This article aims to investigate and examine the relevance of Western civil society theory within non-Western civil society discourse and practice, particularly in the context of civil society in Indonesia. In Western civil society theory, there is an argument that dichotomizes the relationship between civil society and the state, asserting that civil society is a socially constructed institution that exists outside the involvement and domain of the state. Based on this dichotomy, civil society must possess the characteristics of autonomy, independence, and self-generating capacity. This article tests these propositions by using the Indonesian Forum for the Environment (WALHI) and the Indonesian Legal Aid Foundation (YLBHI) as case studies. To achieve this research objective, this study was conducted through in-depth interviews with activists, key figures, and former activists, as well as literature studies using official documents and related publications on WALHI and YLBHI. The findings reveal that applying Western civil society theory in Indonesia requires theoretical revision and modification, including the redefinition of civil society as a social group that may be established solely by society, or jointly by society and the state, with discourse and practical domains shaped by dynamic interactions with the state domain. As a result of this redefinition, it is found that, of the civil society criteria emphasized in Western theory, Indonesian civil society has successfully manifested the characteristic of autonomy, while still striving to realize the characteristics of independence and self-generating capacity. This condition is influenced by the intense interaction between accommodative state policies, international institutional involvement, and the participation of the communities they advocate for, all of which shape the dynamics of civil society’s growth and development in Indonesia.